2019
DOI: 10.1080/21691401.2019.1614014
|View full text |Cite
|
Sign up to set email alerts
|

Orexin A ameliorates HBV X protein-induced cytotoxicity and inflammatory response in human hepatocytes

Abstract: Hepatitis B virus is one of the main causes of hepatitis and hepatocellular carcinoma (HCC). Hepatitis B virus-encoded X protein (HBx) has been shown to be involved in many aspects of the pathogenicity of liver diseases. Orexin A is a small peptide produced in the hippocampus. Orexin A and its receptor have become important therapeutic targets for certain metabolic disorders. In this study, we show that orexin A has a protective role against HBx-induced cytotoxicity and inflammation in hepatocytes. The ectopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…It has been seen that this was attenuated by the pretreatment with OXA, in line with a study by Bihamta et al conducted on cardiomyocyte cells [44]. This is believed to be thanks to the ability of OXA to activate the PI3K/MEK1/2/ERK1/2 signaling pathway and to attenuate the H 2 O 2 -induced increase in apoptosis and decrease in SH-SY5Y cell viability [42]. In another set of experiments, Hah Y.S et al showed how the level of ROS in TNF-α-induced fibroblast-like synoviocytes was found to be reduced in the presence of orexin A.…”
Section: The Orexin Systemsupporting
confidence: 81%
See 1 more Smart Citation
“…It has been seen that this was attenuated by the pretreatment with OXA, in line with a study by Bihamta et al conducted on cardiomyocyte cells [44]. This is believed to be thanks to the ability of OXA to activate the PI3K/MEK1/2/ERK1/2 signaling pathway and to attenuate the H 2 O 2 -induced increase in apoptosis and decrease in SH-SY5Y cell viability [42]. In another set of experiments, Hah Y.S et al showed how the level of ROS in TNF-α-induced fibroblast-like synoviocytes was found to be reduced in the presence of orexin A.…”
Section: The Orexin Systemsupporting
confidence: 81%
“…Among those analyzed [39][40][41], we find a study by Butterick et al [39] that shows how, in a hypothalamic cell line, the use of OXA leads to changes in cell survival following oxidative stress, particularly after H 2 O 2 ; this study, in fact, has demonstrated that OXA is a neuroprotective molecule, partly because it reduces caspase-committed apoptosis and lipid peroxidation. There are also further studies regarding the orexin system and the reduction in oxidative stress, such as s study by Wang et al, which demonstrates how a neuroblastoma cell line reduces its oxidative stress induced by H 2 O 2 following pretreatment with OXA [42]. H 2 O 2 treatment is commonly used to induce oxidative stress [43].…”
Section: The Orexin Systemmentioning
confidence: 99%
“…ROS play an important role in physiological health, and are mainly involved in immune responses, signal transduction and gene expression regulation in vivo (Lou, Li, & Han, ). Studies have shown that ROS is closely related to the activation of the NF‐κB pathway mediated by multiple factors (Nisr, Shah, Ganley, & Hundal, ; Wang, He, Wan, Wang, & Zhang, ). The current results showed that miR‐488 mimics can significantly inhibit LPS‐induced ROS enrichment in BEND cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the levels of 4-HNE, a highly toxic lipid peroxidation product of aldehydes (54), were observed to increase as a result. High 4-HNE levels can induce the release of cytochrome c from the mitochondria by activating the mitogen-activated protein kinase/JNK cell death signal cascade (55). In the cytoplasm, cytochrome c activates caspase-9 and caspase-3, eventually leading to apoptosis of cochlear cells (56,57).…”
Section: Discussionmentioning
confidence: 99%